Studi Literatur: Pengaruh Asupan Energi Protein dan Riwayat ASI Eksklusif terhadap Stunting - I Made Sudarta; Syafruddin Ali Salaka (Jurnal Kesehatan Manarang, 2021)
The incidence of short toddlers commonly referred to as stunting is one of the nutritional problems worldwide. In 2017 22.2% or about 150.8 million toddlers in the world experienced stunting. The Integrated Toddler Nutrition Status Survey (SSGBI) by Balitbangkes Kemenkes Republik Indonesia in 2019 shows that the highest proportion of stunting is found in East Nusa Tenggara, West Sulawesi, and West Nusa Tenggara. The districts in West Sulawesi with the highest percentage of very short and short toddlers at the age of 0 – 59 months in 2018 were Mamuju Regency which is 20.08% and 26.38%. This study aims to determine the influence of protein and energy intake and exclusive breastfeeding history of breastfeeding on stunting events. This research is a literature review that summarizes some relevant literature. Articles searched using google scholar database. After the screening, 21 articles were eligible and met the criteria. There is an influence of protein and energy intake and exclusive breastfeeding on stunting. It is expected that the results of this study will become one of the educational materials and nursing interventions that can be applied in the health service in preventing stunting.